Using PADLET Application in Improving the Tenth Grade Students’ Writing Ability at SMA YADIKA Bandar Lampung - Dewi Hayati Muthmainah; Dameria Magdalena Sidabalok (Linguistic, English Education and Art (LEEA) Journal, 2023)
The purpose of this study was to determine whether the use of the Padlet application had a significant impact on the writing ability of Tenth grade students at SMA Yadika Bandar Lampung. In this study, the researchers uses quantitative research. The study technique employed a quasi-experimental design, and the therapy consisted of three encounters. The basic skills of the pupils are ascertained through a pre-test in this approach prior to therapy. The study's target demographic was the tentth grade at SMA Yadika Bandar Lampung. Science One and Science Two were the two courses from which the samples were obtained. The author uses testing tools to construct descriptive stories about historical sites to collect data for pre-testing and post-testing. The findings indicated that the outcomes of creating descriptive prose were impacted by the Padlet application. The increase in the average score obtained from the pre-test results from 60.15 to 78.09 in the post-test results proves this. The results of hypothesis testing, which is 0.000 less than the Sig value of 0.05, also supports it. In other words, the Padlet application affects the students at SMA Yadika Bandar Lampung in the tenth grade's descriptive text writing skills Keywords: Descriptive Text, Padlet Application, Writing Ability